PENGARUH DIGITAL MARKETING, BRAND AWARENESS, DAN INOVASI PRODUK TERHADAP DAYA SAING UMKM TOKO ROTI GOLDEN ROSE DI KECAMATAN MEDAN TEMBUNG - Jaya, Stefanie Lean; Purba, Mohd. Nawi; Auza, Ara (POLITEKNIK LP3I JAKARTA, 2026)
MSMEs are an important sector in supporting the national economy and are required to be able to adapt to changes in consumer behavior that increasingly rely on information technology, especially the internet. required to be able to adapt to changes in consumer behavior that increasingly rely on information technology such as digital marketing, especially the Golden Rose Bakery located in Medan Tembung. In addition, brand awareness and product innovation are also important factors in determining the competitiveness of a business. High-quality products will not be able to survive in the market if they are not accompanied by brand strength that is easily recognizable and remembered by consumers. The purpose of this research is to test whether the Influence of Digital Marketing, Brand Awareness, and Product Innovation on the Competitiveness of Golden Rose Bakery MSMEs in Medan Tembung District.This study uses primary data and secondary data and uses quantitative descriptive methods, because this study focuses on hypothesis testing with numerical data and statistical analysis by having a sample of 112 respondents using SEM analysis. The results of the research on the Influence of Digital Marketing, Brand Awareness, and Product Innovation on the Competitiveness of MSMEs Golden Rose Bakery in Medan Tembung District achieved the desired results. Therefore, it can be concluded that Digital Marketing affects the competitiveness of MSMEs, Brand Awareness affects the competitiveness of MSMEs, and Product Innovation affects the competitiveness of MSME.